2022
DOI: 10.1021/acsomega.1c06579
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Production by Ethanol Reforming on Supported Ni–Cu Catalysts

Abstract: Supported bimetallic Ni–Cu catalysts with different Ni–Cu loadings on alumina (Al2O3), alumina–silica (Al2O3–SiO2), alumina–magnesia (Al2O3–MgO), alumina–zinc oxide (Al2O3–ZnO), and alumina–lanthanum oxide (Al2O3–La2O3) were prepared and tested in ethanol steam reforming for the production of hydrogen (H2). These catalysts were characterized by X-ray diffraction, H2-temperature-programmed reduction, ammonia-temperature-programmed desorption, X-ray photoelectron spectroscopy, thermogravimetry, and differential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…[82] As a result, adding oxides to alumina is highly recommended to reduce the acidity of the alumina-based support material to minimize coke formation. In this context, Liu et al [83] Ceria (CeO 2 ) was first discovered in 1953 by the US Geological Survey using a spectro-chemical method as a rare earth element. [84] In 1975, CeO 2 was identified as inert support to stabilize active metal nanoparticles for catalytic usage since it had a better capacity for metal dispersion when compared to conventional Al 2 O 3 .…”
Section: Supportsmentioning
confidence: 99%
See 1 more Smart Citation
“…[82] As a result, adding oxides to alumina is highly recommended to reduce the acidity of the alumina-based support material to minimize coke formation. In this context, Liu et al [83] Ceria (CeO 2 ) was first discovered in 1953 by the US Geological Survey using a spectro-chemical method as a rare earth element. [84] In 1975, CeO 2 was identified as inert support to stabilize active metal nanoparticles for catalytic usage since it had a better capacity for metal dispersion when compared to conventional Al 2 O 3 .…”
Section: Supportsmentioning
confidence: 99%
“…[ 82 ] As a result, adding oxides to alumina is highly recommended to reduce the acidity of the alumina‐based support material to minimize coke formation. In this context, Liu et al [ 83 ] used various oxide supports (i.e., Al 2 O 3 , Al 2 O 3 ‐SiO 2 , Al 2 O 3 ‐MgO, Al 2 O 3 ‐ZnO, and Al 2 O 3 ‐La 2 O 3 ) on the bimetallic (Ni‐Cu) catalysts and tested for ESR reactions. Results indicated that incorporation of Cu improved NiO's ability to be reduced.…”
Section: Background: Ethanol To H2 As a Gaseous Productmentioning
confidence: 99%
“…However, nickel suffers from coke formation and sintering. The latter can be inhibited if alloying with Ag or Cu [ 16 , 17 ]. Infiltration is a standard fabrication process to coat the pores of a substrate with the desired catalysts [ 5 , 10 , 11 , 16 , 17 ]: A solution containing the desired cations is impregnated in the porous supports as many times as needed to obtain the desired loading, and the sample is calcined in air to burn out all the organics then reduced to the metallic state.…”
Section: Introductionmentioning
confidence: 99%
“…There is a C–C bond in ethanol, that causes the formation of much coke. Coke deposits on catalysts’ surfaces and deactivates them. Therefore, in the process of ethanol reforming, it is worth using plasma reactors, the operation of which is not disturbed by coke. Zhu and Baránková generated plasma in liquid substrates.…”
Section: Introductionmentioning
confidence: 99%